A technical approach of the audience participation in the performance 'O Chaos das 5' - Araújo, João; de Paulo, Avner; Silva Junior, Igino; Schiavoni, Flávio Luiz; Canito, Mauro César Fachina; Costa, Rômulo Augusto (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10419, 2019)
Since HTML 5 and web audio were released, we have seen several initiatives to construct web based instruments and musical applications based on this technology. Web based instruments involved composers, musicians and the audience in musical performances based in the fact that a web instrument embedded in a web page can be accessed by everyone. Nonetheless, despite the fact that these applications are accessible by the network, it is not easy to use the network and these technologies to synchronize the participants of a musical performance and control the level of interaction in a collaborative musical creation scenario. Based on a multimedia performance created in our research group, O Chaos das 5, we present in this paper some scenarios of interaction and control between musicians and the audience that can be reached using a server side programming infrastructure along with the HTML5. In this performance, the audience took part of the musical soundscape using a cellphone to access a set of digital instruments. These scenarios and the proposed solutions brought up a set of possibilities to balance control and interaction of audience participation into live performance using web instruments.